2019
DOI: 10.1088/1361-6528/ab5a0e
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-enhanced fluorescence in gold nanorod-quantum dot coupled systems

Abstract: Plasmon-exciton coupling is of great importance to many optical devices and applications. One of the coupling manifestations is plasmon-enhanced fluorescence. Although this effect is demonstrated in numerous experimental and theoretical works, there are different particle shapes for which this effect is not fully investigated. In this work electrostatic complexes of gold nanorods and CdSe/CdZnS quantum dots were studied. Double-resonant gold nanorods have an advantage of the simultaneous enhancement of the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 74 publications
(88 reference statements)
3
23
0
Order By: Relevance
“…Comparison of the PL spectra indicates that an enhancement factor of ≈36 was achieved with the AuNRs (Figure 3e). This enhancement factor is approximately three times higher than Au nanorods [39] and six times higher than Ag microrings. [40] Fluorescence-lifetime spectra of the QDs show a decay time of 3.6 ns on the AuNRs, which is three times faster than that without AuNRs (Figure 3f).…”
Section: Laser-directed Solid-state Growth Of Gold Nanowire Derivativesmentioning
confidence: 82%
“…Comparison of the PL spectra indicates that an enhancement factor of ≈36 was achieved with the AuNRs (Figure 3e). This enhancement factor is approximately three times higher than Au nanorods [39] and six times higher than Ag microrings. [40] Fluorescence-lifetime spectra of the QDs show a decay time of 3.6 ns on the AuNRs, which is three times faster than that without AuNRs (Figure 3f).…”
Section: Laser-directed Solid-state Growth Of Gold Nanowire Derivativesmentioning
confidence: 82%
“…Therefore, it is quite meaningful to wrap Al 2 O 3 material on the Au core shell. At the same distance, there is a certain difference in the Raman enhancement factor under different excitation wavelengths, but it is basically in an order of magnitude, which also shows that the Au dimer has a wider excitation spectrum under different distance, making its application scope wider 27 . Figure 6 shows that the in uence of excitation wavelength on the nal Raman enhancement factor of the nal model with the increase of the thickness of Al 2 O 3 , however the in uence of excitation wavelength on the nal Raman enhancement factor of Au dimer increases with the increase of distance.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, this may be a result of the enhanced absorption. 11 Regarding TPE PL, several studies have previously shown its strong enhancement in fluorescent organic dyes placed at the very short distances from metal nanostructures. [12][13][14][15][16][17] However, in these studies, the spectral conditions of the resonance between the plasmon modes and the fluorescence and absorption bands of the molecules were not specified, which made it difficult to correctly interpret the results.…”
Section: Introductionmentioning
confidence: 99%